Sodium Contents in Dairy Cow Urine and Soil Aggregate Sizes Influence the Amount of Nitrogen Lost from Soil. (12th November 2015) - Hamamoto, Toru; Uchida, Yoshitaka
Abstract : Cow urine deposition on pasture soils is a major source of N-related environmental impacts in the dairy farming systems. The urine-N can potentially be lost to the ground water as nitrate (N O 3 - ) and to the atmosphere as nitrous oxide (N2 O). These N-related environmental impacts are possibly related to the sodium (Na + ) concentrations in urine. We sampled a pasture soil and separated it into three aggregate size groups (0–3, 3–5, and 5–7 mm). Then, cow urine with variable Na + concentrations (4.3–6.1 g Na +  L −1 ) was added to the soil cores. We treated the cores with simulated heavy rains and measured the amounts of calcium (Ca 2+ ), Na +, potassium (K + ), and inorganic-N leached from the soils. N2 O emission rates were also determined throughout the experimental period. Increasing Na + concentration in urine decreased the loss ofN O 3 - (−20%), after repeatedly applied simulated rain treatments (30 mm × 3), whereas it increased the loss of ammonium (31%) and K + (19%). For the loss of Ca 2+ and the emissions of N2 O, the effect of the Na + concentrations was unclear. Field level studies and studies focusing on the mechanisms behind the changes in nutrient losses are needed.